Program Perpustakaan dalam Mengatasi “Library Anxiety” - Sari, Dita Indah; Sayekti, Retno (Syarif Hidayatullah State Islamic University of Jakarta, 2023)
Libraries are valuable assets in the acquisition of knowledge, but often individuals, especially students, face